Prioritizing primary care in HIV: comorbidity, toxicity, and demography. - Justice, Amy C (Topics in HIV medicine : a publication of the International AIDS Society, USA, 2006)
Mortality among HIV-infected patients after the first year of antiretroviral therapy has not improved in recent years. Future improvement in survival may come partly through earlier diagnosis and institution of treatment and by maximizing treatment adherence. However, outcomes in HIV disease are also influenced today by long-term treatment toxicities, non-HIV-specific comorbid conditions, and comorbid behaviors. Primary care efforts to improve outcomes should be focused on health behaviors (eg, adherence, elimination of substance abuse, diet, and exercise) and effective management of conditions such as hypertension and depression, since successful intervention in these areas reduces risk of a variety of conditions associated with mortality in HIV disease. Issues in prioritizing primary care in HIV disease were discussed by Amy C. Justice, MD, PhD, at the 9th Annual Ryan White CARE Act Clinical Update in Washington, DC. The original presentation is available as a Webcast at www.iasusa.org.
Keywords: Antiretroviral Therapy, Highly Active; Comorbidity; Demography; Diet; Exercise; HIV Infections; Humans; Patient Compliance; Primary Health Care; Substance-Related Disorders